Mathematic Score of the Champions - Iskandar, Bayu; Haryono, Haryono; Utanto, Yuli (Innovative Journal of Curriculum and Educational Technology, 2019)
Mathematics is still a shortcoming for primary school children. Various studies were conducted to improve the learning results of mathematics. Unexpectedly there was a phenomenon in a remote place, under the foot of Mount Lawu, which was a primary school that had been ranked in the top ten of the National and 5 of Central Java Province to achieve the National Mathematics exam scores. The primary school is Public Elementary School 03 Bandardawung. Good scores of students at Public Elementary School 03 Bandardawung are still stable today. This study aims to determine the learning and causes of excellence of students at Public Elementary School 03 Bandardawung in Mathematics. The research method uses qualitative descriptive-analytical with phenomenological design. The results showed: First, planning of learning in the design according to the materials and needs of the students and following the prevailing rules. Second, the implementation of learning is implemented in the student center with media optimization. Third, evaluation is done from the process to the end, there is a repetition system, where if there are students who do not understand, it will be repeated continuously until the student understands. Fourth, the competency of teachers is good, demonstrated by the fulfillment of four teachers competence and ten basic teaching techniques. Fifth, the school, community, and family environment fully support learning. Synergy, support, and high dedication from all elements make learning so optimal. The benefit of research is to provide an overview of how potential Mathematics learning can be used widely because it has proven its good results over the years at Public Elementary School 03 Bandardawung.